Energy Efficiency: The Manufacturing Sector in Indonesia - Hariyanto, Bayu (JEJAK: Jurnal Ekonomi dan Kebijakan, 2021)
Indonesia is involved in the global effort to alleviate the deterioration of the environment due to climate change. Given that the manufacturing industry accounts for the second-highest share of national energy consumption, efficiency energy in the industrial sector is crucial. This research examines which industrial subsector has to be prioritized to improve energy efficiency and what are the determinant factors that influence energy efficiency in Indonesia manufacturing. This study analyzes energy intensity as an approach to measure energy efficiency. Focusing on the 2010 - 2015 period, this research employs two methods, namely input-output and panel data regression analysis. The empirical finding shows that textiles and textile products; pulp, paper, paper products, printing, and publishing; and rubber and plastics sectors are the first priority subsectors that must implement green industry standards. The next priority is the subsectors at the second level but have no green industrial standards, namely electrical and optical equipment. Furthermore, there were four variables that statistically increase energy intensity, namely lagged energy intensity, technology intensity, lagged value added, and location of plant. However, other two variables, the price of electricity and company size, can reduce energy intensity.